Holistic, emission, and cost optimization of non-residential building energy systems based on OpenBIM - Jonatan Höpp; David Jansen; Nico Fuchs; Dirk Müller (Energy and Buildings, 2026)

Practical, near-optimal design rule extraction for heat pumps in single-family buildings - Fabian Römer; Nico Fuchs; Dirk Müller (Energy and Buildings, 2026)

Attenuated but not virulent pseudorabies virus activates porcine bone marrow-derived dendritic cells - Emily C. Ashley; Walter Fuchs; Barbara G. Klupp; Dirk Werling; Simon P. Graham; Jane C. Edwards (Veterinary Immunology and Immunopathology, 2025)

Reconciling Gene Tree Discordance and Biogeography in European Crows - Chyi Yin Gwee; Dirk Metzler; Jérôme Fuchs; Jochen B. W. Wolf (Molecular Ecology, 2025)
Reconstructing the evolutionary history of young lineages diverging with gene flow is challenging due to factors like incomplete lineage sorting, introgression, and selection causing gene tree discordance. The European crow hybrid zone between all‐black carrion crows and grey‐coated hooded crows exemplifies this challenge. Most of the genome in Western and Central European carrion crow populations is near‐identical to hooded crows, but differs substantially from their Iberian congeners. A notable exception is a single major‐effect colour‐locus under sexual selection aligning with the ‘species’ tree. To understand the underlying evolutionary processes, we reconstructed the biogeographic history of the species complex. During the Pleistocene carrion and hooded crows took refuge in the Iberian Peninsula and the Middle East, respectively. Allele‐sharing of all‐black Western European populations with likewise black Iberian crows at the colour‐locus represents the last trace of carrion crow ancestry, resisting gene flow from expanding hooded crow populations that have homogenised most of the genome. A model of colour‐locus introgression from an Iberian ancestor into hooded crow populations near the Pyrenées was significantly less supported. We found no positive relationship between introgression and recombination rate consistent with the absence of genome‐wide, polygenic barriers in this young species complex. Overall, this study portrays a scenario where few large‐effect loci, subject to divergent sexual selection, resist rampant and asymmetric gene exchange. This study underscores the importance of integrating population demography and biogeography to accurately interpret patterns of gene tree discordance following population divergence.

Warming-induced destabilization of polar coastal rock cliffs and the role of thermokarst: A case study of Forkastningsfjellet on Svalbard - Dirk Kuhn; Reginald L. Hermanns; Michael Fuchs; Nick Schüßler; Jewgenij Torizin; Juditha Aga; Jacob Bendle; Trond Eiken; Dirk Balzer (Science of The Total Environment, 2025)

Project ‘‘Mass Movements in Germany’’ and its implications for nationwide landslide susceptibility assessment - Jewgenij Torizin; Michael Fuchs; Dirk Balzer; Dirk Kuhn; Stefan Glaser; Dominik Ehret; Johannes Wiedenmann; Peter Dommaschk; Stefan Henscheid; Roland Strauß (Bulletin of Engineering Geology and the Environment, 2024)
The paper presents the framework and discusses the outcomes of the "Mass Movements in Germany" project—a collaboration of five State Geological Surveys (SGSs) and the Federal Institute for Geosciences and Natural Resources (BGR) to conduct a feasibility study for a nationwide landslide susceptibility map in Germany using harmonized datasets. Therefore, distinct methods representing heuristic, physically-based, and data-driven approaches were employed. In 14 consecutive modeling cases, we investigated parameter selection and preparation, model building, evaluation, and transferability issues. The results show that nationally harmonized datasets, deemed high-quality, exhibited data generalization at regional scales, affecting the reliability of the landslide susceptibility patterns. While using regional datasets on larger scales mitigated some generalization effects, heterogeneities in inventory datasets among distinct federal states pose challenges in creating a nationwide applicable model. Heterogeneous data require locally adjusted model designs affecting the model's transferability and comparability of data-driven models across large regions. Heuristic methods operate without observational data but require in-depth knowledge of the regional-geological conditions by involving expert groups rather than single experts. The physically-based model shows promising results with parametrization based on the pedotransfer functions and soil database supplementing the national soil map. However, this approach is limited to shallow translational landslides. Thus, considering all mass movement types, a single comprehensive approach for creating a nationwide landslide susceptibility map for Germany is currently not feasible. Close collaboration and further harmonization of datasets and methods involving all SGSs are needed.

Correction to: Picking up speed: cell cycle regulation during effector CD8+ T cell differentiation - Lorenz Kretschmer; Noémie Fuchs; Dirk H. Busch; Veit R. Buchholz (Medical Microbiology and Immunology, 2023)

Picking up speed: cell cycle regulation during effector CD8+ T cell differentiation - Lorenz Kretschmer; Noémie Fuchs; Dirk H. Busch; Veit R. Buchholz (Medical Microbiology and Immunology, 2023)
Clonal expansion and development of immunological memory are two hallmarks of adaptive immune responses. Resolving the intricate pathways that regulate cell cycle activity and lead to the generation of diverse effector and memory T cell subsets is essential for improving our understanding of protective T cell immunity. A deeper knowledge of cell cycle regulation in T cells also has translational implications for adoptive cell therapies and vaccinations against infectious diseases. Here, we summarize recent evidence for an early diversification of effector and memory CD8 + T cell fates and discuss how this process is coupled to discrete changes in division speed. We further review technical advances in lineage tracing and cell cycle analysis and outline how these techniques have shed new light on the population dynamics of CD8 + T cell responses, thereby refining our current understanding of the developmental organization of the memory T cell pool.

A comprehensive phenotypic characterization of a whole-body Wdr45 knock-out mouse - Caroline A. Biagosch; Silvia Vidali; Michael Faerberboeck; Svenja-Viola Hensler; Lore Becker; Oana V. Amarie; Antonio Aguilar-Pimentel; Lillian Garrett; Tanja Klein-Rodewald; Birgit Rathkolb; Enrica Zanuttigh; Julia Calzada-Wack; et al. (Mammalian Genome, 2021)
Pathogenic variants in the WDR45 (OMIM: 300,526) gene on chromosome Xp11 are the genetic cause of a rare neurological disorder characterized by increased iron deposition in the basal ganglia. As WDR45 encodes a beta-propeller scaffold protein with a putative role in autophagy, the disease has been named Beta-Propeller Protein-Associated Neurodegeneration (BPAN). BPAN represents one of the four most common forms of Neurodegeneration with Brain Iron Accumulation (NBIA). In the current study, we generated and characterized a whole-body Wdr45 knock-out (KO) mouse model. The model, developed using TALENs, presents a 20-bp deletion in exon 2 of Wdr45 . Homozygous females and hemizygous males are viable, proving that systemic depletion of Wdr45 does not impair viability and male fertility in mice. The in-depth phenotypic characterization of the mouse model revealed neuropathology signs at four months of age, neurodegeneration progressing with ageing, hearing and visual impairment, specific haematological alterations, but no brain iron accumulation. Biochemically, Wdr45 KO mice presented with decreased complex I (CI) activity in the brain, suggesting that mitochondrial dysfunction accompanies Wdr45 deficiency. Overall, the systemic Wdr45 KO described here complements the two mouse models previously reported in the literature (PMIDs: 26,000,824, 31,204,559) and represents an additional robust model to investigate the pathophysiology of BPAN and to test therapeutic strategies for the disease.

A comprehensive and comparative phenotypic analysis of the collaborative founder strains identifies new and known phenotypes - Heike Kollmus; Helmut Fuchs; Christoph Lengger; Hamed Haselimashhadi; Molly A. Bogue; Manuela A. Östereicher; Marion Horsch; Thure Adler; Juan Antonio Aguilar-Pimentel; Oana Veronica Amarie; Lore Becker; Johannes Beckers; et al. (Mammalian Genome, 2020)
The collaborative cross (CC) is a large panel of mouse-inbred lines derived from eight founder strains (NOD/ShiLtJ, NZO/HILtJ, A/J, C57BL/6J, 129S1/SvImJ, CAST/EiJ, PWK/PhJ, and WSB/EiJ). Here, we performed a comprehensive and comparative phenotyping screening to identify phenotypic differences and similarities between the eight founder strains. In total, more than 300 parameters including allergy, behavior, cardiovascular, clinical blood chemistry, dysmorphology, bone and cartilage, energy metabolism, eye and vision, immunology, lung function, neurology, nociception, and pathology were analyzed; in most traits from sixteen females and sixteen males. We identified over 270 parameters that were significantly different between strains. This study highlights the value of the founder and CC strains for phenotype-genotype associations of many genetic traits that are highly relevant to human diseases. All data described here are publicly available from the mouse phenome database for analyses and downloads.

First Middle–Late Jurassic gladius vestiges provide new evidence on the detailed origin of incirrate and cirrate octopuses (Coleoidea) - Dirk Fuchs; Günter Schweigert (PalZ, 2018)

Statistical landslide susceptibility assessment in a dynamic environment: A case study for Lanzhou City, Gansu Province, NW China - Jewgenij Torizin; Li-chao Wang; Michael Fuchs; Bin Tong; Dirk Balzer; Li-qin Wan; Dirk Kuhn; Ang Li; Liang Chen (Journal of Mountain Science, 2018)

First record of a xiphoteuthidid coleoid (Cephalopoda: Aulacoceratida) from the Germanic Triassic (Erfurt Formation, Ladinian) - Günter Schweigert; Dirk Fuchs; Hans Michael Salomon (PalZ, 2016)

A nearly complete respiratory, circulatory, and excretory system preserved in small Late Cretaceous octopods (Cephalopoda) from Lebanon - Dirk Fuchs; Philipp R. Wilby; Sigurd von Boletzky; Pierre Abi-Saad; Helmut Keupp; Yasuhiro Iba (PalZ, 2016)

First record of a complete arm crown of the Early Jurassic coleoid Loligosepia (Cephalopoda) - Dirk Fuchs; Helmut Keupp; Günter Schweigert (PalZ, 2013)

Clone libraries and single cell genome amplification reveal extended diversity of uncultivated magnetotactic bacteria from marine and freshwater environments - Sebastian Kolinko; Gerhard Wanner; Emanuel Katzmann; Felizitas Kiemer; Bernhard M. Fuchs; Dirk Schüler (Environmental Microbiology, 2013)
Summary Magnetotactic bacteria ( MTB ), which orient along the earth's magnetic field using magnetosomes, are ubiquitous and abundant in marine and freshwater environments. Previous phylogenetic analysis of diverse MTB has been limited to few cultured species and the most abundant and conspicuous members of natural populations, which were assigned to various lineages of the P roteobacteria , the N itrospirae phylum as well as the candidate division OP 3. However, their known phylogenetic diversity still not matches the large morphological and ultrastructural variability of uncultured MTB found in environmental communities. Here, we used analysis of 16 S rRNA gene clone libraries in combination with microsorting and whole‐genome amplification to systematically address the entire diversity of uncultured MTB from two different habitats. This approach revealed extensive and novel diversity of MTB within the freshwater and marine sediment samples. In total, single‐cell analysis identified eight different phylotypes, which were only partly represented in the clone libraries, and which could be unambiguously assigned to their respective morphotypes. Identified MTB belonged to the A lphaproteobacteria (seven species) and the N itrospirae phylum (two species). End‐sequencing of a small insert library created from WGA ‐derived DNA of a novel conspicuous magnetotactic vibrio identified genes with highest similarity to two cultivated MTB as well as to other phylogenetic groups. In conclusion, the combination of metagenomic cloning and single cell sorting represents a powerful approach to recover maximum bacterial diversity including low‐abundant magnetotactic phylotypes from environmental samples and also provides access to genomic analysis of uncultivated MTB .

Innovations in phenotyping of mouse models in the German Mouse Clinic - Helmut Fuchs; Valérie Gailus-Durner; Susanne Neschen; Thure Adler; Luciana Caminha Afonso; Juan Antonio Aguilar-Pimentel; Lore Becker; Alexander Bohla; Julia Calzada-Wack; Christian Cohrs; Anna Dewert; Barbara Fridrich; et al. (Mammalian Genome, 2012)

Glyphiteuthis rhinophora n. sp., a trachyteuthidid (Coleoidea, Cephalopoda) from the Cenomanian (Late Cretaceous) of Mexico - Dirk Fuchs; Wolfgang Stinnesbeck; Christina Ifrim; Samuel Giersch; José Manuel Padilla Gutierrez; Eberhard Frey (PalZ, 2010)

Microphthalmia, parkinsonism, and enhanced nociception in Pitx3 416insG mice - Michael Rosemann; Alesia Ivashkevich; Jack Favor; Claudia Dalke; Sabine M. Hölter; Lore Becker; Ildikó Rácz; Ines Bolle; Martina Klempt; Birgit Rathkolb; Svetoslav Kalaydjiev; Thure Adler; et al. (Mammalian Genome, 2010)